Penerapan Akupresure dan Massage Teknik Friction sebagai Upaya Menurunkan Nyeri Punggung Ibu Usia Kehamilan 27-40 Minggu - Kurniyati, Eka Meiri; Indriyani, Ratna; Wardita, Yulia; Suprayitno, Emdat (Journal Of Health Science (Jurnal Ilmu Kesehatan), 2022)
As much as 54.9% in the third trimester of pregnancy, most pregnant women experience lower back pain as much as 10% of pregnant women who experience chronic low back pain. One of the efforts to reduce low back pain is with acupressure, at point BL 23 and massage with friction techniques for 10 minute. At the Gapura Health Center from January to April 2022, 30% of pregnant women in the third trimester complained of back pain. The purpose of this study was to determine the application of acupressure at the BL 23 point and friction massage as an effort to reduce back pain in third trimester pregnant women. As much as 54.9% in the third trimester of pregnancy, most pregnant women experience lower back pain as much as 10% of pregnant women who experience chronic low back pain. One of the efforts to reduce low back pain is with acupressure, at point BL 23 and massage with friction techniques for 10 minute. At the Gapura Health Center from January to April 2022, 30% of pregnant women in the third trimester complained of back pain. The purpose of this study was to determine the application of acupressure at the BL 23 point and friction massage as an effort to reduce back pain in third trimester pregnant women.